Interlimb Asymmetries Identified Using the Rate of Torque Development in Ballistic Contraction Targeting Submaximal Torques - Boccia, Gennaro; Brustio, Paolo Riccardo; Buttacchio, Giampiero; Calabrese, Marzia; Bruzzone, Marco; Casale, Roberto; Rainoldi, Alberto (Frontiers in Physiology, 2018)
Evaluating the rate of torque development (RTD) in isometric ballistic contraction targeting submaximal torques is usually overlooked in the literature. In a series of isometric ballistic contractions targeting a range of submaximal torque values, there is a linear relationship between the peak torque and the peak RTD obtained in each contraction. RTD-SF represents the slope of this relationship. In this study, we investigated the prevalence of interlimb asymmetry in the RTD-SF and in the RTD calculated across submaximal torques. Furthermore, we compared these asymmetry indices with those calculated adopting more classical approaches such as ballistic contraction targeting maximal torque and isokinetic concentric conditions. Quadriceps and hamstrings strength was evaluated in both limbs of elite under 17 and under 19 soccer players (20 males, 17±1 years). Participants performed three concentric isokinetic contractions at 240°/s and a series of isometric ballistic contractions targeting from 20% to 100% of maximal isometric torque. The interlimb difference was calculated for each parameter and players presenting an interlimb difference > 15% were identified. A total of 40% (for quadriceps) and 60% (for hamstring) of players showed an interlimb asymmetry in isometric RTD for at least 50% of submaximal torque range. The RTD-SF was able to identify more players with asymmetry than the classical isokinetic tests. However, isokinetic and isometric indices of asymmetry were in general poorly or not correlated with each other. Most players presented an interlimb asymmetry in RTD for a wide part of the torque range and the adopted protocol was able to highlight important interindividual differences. Furthermore, players showed a large prevalence of RTD-SF asymmetry both in quadriceps and hamstrings. It is still to be determined if these asymmetries are functionally relevant. Nevertheless, the adopted protocol provided meaningful information for identifying interlimb asymmetries that could not be gathered when adopting the classical method of ballistic contractions targeting only maximal torques.